Reconstructing the caliphate or bringing liberal democracy to Turkey?: Millî Görüş’s view on liberal democracy before reaching power - Rosenberg, Uri (Middle Eastern studies, 2024)
This article explores the ideas of the Turkish-Islamist Millî Görüş movement on liberal democracy. From its formation in the 1970s to the 1990s, when it won the Turkish elections, the movement exhibited a substantial shift in their discourse. Millî Görüş started off as a movement with solid anti-Western rhetoric. It openly endorsed revolutionary-Jihadist movements and advocated for an Islamic state throughout the Muslim world (including, albeit subtly, in Turkey). It supported the 1979 Iranian revolution and argued democracy is a political system that is against Islamic revelation. However, by the mid-late 1990s, the Millî Görüş and its political party presented liberal ideas about the need for Turkey to democratize and respect people’s fundamental rights and freedoms. This rapid intellectual shift within two and a half decades is puzzling.
Publikationsdatum: 17. April 2024 (online)
Gesehen am 22.07.2024